Current Status of Aquarium Fish (Ornamental Fish) Enterprises During the Pandemic Period (Elazig City Sample) - Bulut, Hilal; Ozcan, Ebru Ifakat (My University, 2022)
This study was carried out in order to reveal the situation of aquarium sales enterprises in Elazig and \rto determine their problems. In the study, a total of 14 enterprises (aquarist) were asked questions by \rthe survey method. It has been determined that a significant part of the existing enterprises is located \rin the center of Elazig (93%), all of them continue to operate as tenants and their operating periods \rare over 5 years. It has been noted that 86% of the personnel working in the enterprises are male and \r14% are female. It was determined that the most sold fish species in the research area were 2 fish \rspecies belonging to 2 families. It has been observed that one of the important problems in aquarium \rbusinesses is fish diseases. It has been determined that 93% of the fish sales of the Covid-19 pandemic \rperiod were negatively affected and 7% were positively affected.\r
Keywords: Balıkçılık; İşletme